1993
DOI: 10.1021/jm00054a009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of 2-pyridinone derivatives as specific HIV-1 reverse transcriptase inhibitors. 3. Pyridyl and phenyl analogs of 3-aminopyridin-2(1H)-one

Abstract: In an ongoing effort to develop novel nonnucleoside, specific human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) inhibitors, a series of 3-[(pyridylmethyl)amino]- and 3-[(phenylmethyl)amino]-2-pyridinone derivatives was synthesized and tested for HIV-1 RT inhibitory activity. The more potent compounds have a 2'-methoxy group and 4'- and/or 5'-aliphatic substituents on the pyridyl and phenyl rings. Several of the more potent compounds were also evaluated for antiviral activity in MT-4 cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…These include N-methylation, O-methylation, deletion of one or both alkyl groups and substituting 5-ethyl with 5-methyl. Some structure-activity studies have also been done replacing the benzoxazole by a pyridyl or a phenyl (Wai et al, 1993) (Table 24). It was found that maximum enzyme inhibition was obtained with compounds containing a 2′-methoxy group on either the phenyl or pyridyl ring.…”
Section: Pyridinonesmentioning
confidence: 99%
See 1 more Smart Citation
“…These include N-methylation, O-methylation, deletion of one or both alkyl groups and substituting 5-ethyl with 5-methyl. Some structure-activity studies have also been done replacing the benzoxazole by a pyridyl or a phenyl (Wai et al, 1993) (Table 24). It was found that maximum enzyme inhibition was obtained with compounds containing a 2′-methoxy group on either the phenyl or pyridyl ring.…”
Section: Pyridinonesmentioning
confidence: 99%
“…†Concentration of compound that inhibits the spread of HIV-1 infection in MT-4 cells, by ≥95% using a p24 core antigen ELISA assay. Data from Wai et al (1993). *The concentration that produced 50% inhibition of RT using a rC.dG template primer, and stated as the mean of at least three determinations ±SEM.…”
Section: Pyridinonesmentioning
confidence: 99%
“…In vitro biological data for a series of 38 pyridinone derivatives [8] having HIV-1 RT inhibitory activity was used for the present studies. These derivatives were evaluated for inhibiting the spread of HIV-1 infection in MT-4 cell culture [8].…”
Section: Datasetmentioning
confidence: 99%
“…These derivatives were evaluated for inhibiting the spread of HIV-1 infection in MT-4 cell culture [8]. The HIV-RT inhibitory activity was expressed as pIC 50 .…”
Section: Datasetmentioning
confidence: 99%
“…[26] Binding Mode into the NNRTIs Binding Pocket Automated docking and 3D-QSAR of Merck pyridinones As mentioned earlier, biological experiments showed that A C H T U N G T R E N N U N G L-697,661, L-697,639, L-696,229, and other related Merck pyridinones should bind in the NNRTIs pocket. Several two-dimensional quantitative structure-activity relationship analyses (2D-QSAR) have been performed for this subtype of pyridinone analogue, [9,11,12,29] suggesting a hydrophobic character of their binding site. [30,31] However, no crystal structures of HIV-1 RT in complex with Merck pyridinones are available.…”
Section: Discovery and Developmentmentioning
confidence: 99%